1999
DOI: 10.1074/jbc.274.8.5083
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Reduction of Nucleoside Triphosphate Hydrolase by Antisense RNA Inhibits Toxoplasma gondii Proliferation

Abstract: In the present study, we have generated an antisense NTP RNA construct in which the 3-untranslated region is replaced by a hammerhead ribozyme. The constitutive synthesis of the chimeric antisense RNA-ribozyme construct in parasites that were stably transfected with this construct resulted in a dramatic reduction in the steady-state levels of NTPase. This inhibition was accompanied by a decrease in the capacity of the parasites to replicate. The reduction in parasite proliferation was due to a specific effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 42 publications
4
55
0
2
Order By: Relevance
“…In T. brucei, a combination of efficient RNAi and a tight tet-regulated transcription is routinely applied for large scale analysis of genome function. In contrast, the efficiency of RNAi in apicomplexans is still a matter of debate [85,86], even if previous and more recent studies have reported the successful use of antisense/ribozyme in T. gondii [87][88][89] and some studies have suggested that the mechanism of RNAi can operate in the malaria parasites [90][91][92].…”
Section: Experimental Approaches and Tools Developed To Regulate Genementioning
confidence: 93%
“…In T. brucei, a combination of efficient RNAi and a tight tet-regulated transcription is routinely applied for large scale analysis of genome function. In contrast, the efficiency of RNAi in apicomplexans is still a matter of debate [85,86], even if previous and more recent studies have reported the successful use of antisense/ribozyme in T. gondii [87][88][89] and some studies have suggested that the mechanism of RNAi can operate in the malaria parasites [90][91][92].…”
Section: Experimental Approaches and Tools Developed To Regulate Genementioning
confidence: 93%
“…Processing of ␤-Lactamase Protein (BLA)-To construct a plasmid for transient expression of BLA secretion reporter protein, a fragment encoding BLA was amplified from pBluescript, cloned into the plasmid pNTP/sec vector (a kind gift from Dr. Keith Joiner), and used to transfect the HXGPRT-deficient mutant of T. gondii RH tachyzoites as described previously (17). To assess the effect of a cathepsin C proteinase inhibitor on BLA protein processing in vivo, monolayers of fibroblasts in T25 flasks were infected with RH (BLA) tachyzoites (2 ϫ 10 7 ) for 24 h at 37°C in medium alone or containing 100 M GF-DMK (MP Biomedicals).…”
Section: Methodsmentioning
confidence: 99%
“…The foreign protein is transported in dense granules and secreted into the vacuolar space. Once released, the BLA is rapidly degraded in the parasitophorous vacuole (PV) (17). When parasites were treated with the cathepsin C inhibitor, GF-DMK, however, degradation of BLA was prevented (Fig.…”
Section: Tgcpc Degrades Proteins In the Parasitophorous Vacuole (Pv) mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rhoptry genes are often part of multigene families, and/or are tandemly repeated (Beckers et al, 1996), further complicating a gene knockout approach. To circumvent these problems, we applied a recently developed ribozyme-modified antisense RNA strategy (Nakaar et al, 1999;Nakaar et al, 2000) to lower the expression of ROP2 gene. In this review we show that targeted depletion of ROP2 results in: (1) disruption of rhoptry biogenesis and an impairment of cytokinesis; (2) reduction in the association of host cell mitochondria with PVM of the parasite, and a reduced sterol uptake from the host cell; (3) reduced capacity of parasites to invade and replicate in human fibroblasts, and attenuation of virulence in mice.…”
Section: Introductionmentioning
confidence: 99%